Isolation, Identification And Antibiotic Sensitivity Of Bacterial Isolates From Bovine Mastitis Milk - Govindan , Balakrishnan (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Milk samples collected aseptically from cows suffering from mastitis were examined for bacterial growth. A total of 30 bacterial isolates comprising Eschericia coli, Staphylococcus aureus, Streptococcus agalactiae, Streptococcus disgalactiae, Streptococcus uberis and Pseudomonas aeruginosa were isolated from the milk samples. In vitro antibiogram of these isolates revealed higher sensitivity for Fluoroquinolones (Ciprofloaxacin. Enrofloxacin and Pefloxacin). The results of this study suggested Fluoroquinolones (Ciprofloxacin. Enrofloxacin and Pefloxacin) as the drug of choice for treatment of bovine mastitis.
Keywords: Bovine Mastitis; Bacteria; Antibiogram